2019
DOI: 10.3390/cancers11040508
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Regulation of HOX Transcription Factors

Abstract: The HOX genes are a group of homeodomain-containing transcription factors that play important regulatory roles in early development, including the establishment of cell and tissue identity. HOX expression is generally reduced in adult cells but is frequently re-established as an early event in tumour formation and supports an oncogenic phenotype. HOX transcription factors are also involved in cell cycle regulation and DNA repair, along with normal adult physiological process including stem cell renewal. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…In particular, phosphorylation of the S204 residue by PKC strongly decreased HOXA9/DNA and HOXA9/PBX1/DNA complex formation in vitro, and PKC inhibition by bisindolyl-maleamide 1 decreases TPA-induced differentiation in a HOXA9-transformed murine cell line [107] (Figure 3, point t). Many other HOX proteins are also subjected to phosphorylation by PKC, CKII, cyclin-dependent kinase (CDK), MAPK, ATM/ATR, and other kinases as recently reviewed [312], but the precise function of many is still unclear and no therapeutic approaches have yet been developed in clinical trials, even if it has been shown that PKC inhibition by Ro31 enhances the effect of HXR9 peptide on necroptosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, phosphorylation of the S204 residue by PKC strongly decreased HOXA9/DNA and HOXA9/PBX1/DNA complex formation in vitro, and PKC inhibition by bisindolyl-maleamide 1 decreases TPA-induced differentiation in a HOXA9-transformed murine cell line [107] (Figure 3, point t). Many other HOX proteins are also subjected to phosphorylation by PKC, CKII, cyclin-dependent kinase (CDK), MAPK, ATM/ATR, and other kinases as recently reviewed [312], but the precise function of many is still unclear and no therapeutic approaches have yet been developed in clinical trials, even if it has been shown that PKC inhibition by Ro31 enhances the effect of HXR9 peptide on necroptosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Homeobox genes (HOX genes) are an important family of genes regulating embryonic development and cell growth and differentiation in vivo. With the continuous development of the understanding of HOX genes, recent studies have found that HOX genes are closely related to the occurrence, development, invasion and metastasis of tumors 20,21. Studies have shown that HOX gene plays a positive or negative regulatory role in the process of cell proliferation and differentiation, and is closely related to the occurrence and development of gastrointestinal tumors, breast cancer, endometrial cancer, etc 21.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of the understanding of HOX genes, recent studies have found that HOX genes are closely related to the occurrence, development, invasion and metastasis of tumors 20,21. Studies have shown that HOX gene plays a positive or negative regulatory role in the process of cell proliferation and differentiation, and is closely related to the occurrence and development of gastrointestinal tumors, breast cancer, endometrial cancer, etc 21. As a member of the HOX family, HOXA9 gene may be a new tumor molecular marker protein, which may play an important role in the development of ECa 22,23.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports have demonstrated that mis-regulation of HOX genes expression plays key roles in the development of cancers. Only in the last five years have more than 50 reviews related to this subject been published; see, for example, References [4,[8][9][10][11]. However, such studies were typically based on different technologies used in different labs and analyzed by different computational tools.…”
Section: Introductionmentioning
confidence: 99%